2021
DOI: 10.1088/1757-899x/1126/1/012035
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of Drilling Parameters of Metal Matrix Composites using Genetic Algorithm in the Taguchi Method

Abstract: This work presents the machining parameters optimization on machining metal matrix composites using genetic algorithm in the Taguchi method with the objectives of minimization of surface roughness, cutting force, maximization of metal removal rate, cutting power, specific cutting energy, cutting power and machining time. Experiments were conducted on aluminium silicon carbide Metal Matrix composite using TiN coated HSS twist drills. Optimal setting of parameters have been identified using Taguchi Technique and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…It was noticed that minimum wear rate for alumina composite could be achieved at 5 wt% reinforcement. Rao et al [18] applied GA and Taguchi methodology to optimize the drilling parameters for AlSiC MMC. Bongale et al [19] attempted to minimize wear on Al/SiCnp/E-glass fiber MMC while adopting Taguchi methodology and GA technique.…”
Section: Introductionmentioning
confidence: 99%
“…It was noticed that minimum wear rate for alumina composite could be achieved at 5 wt% reinforcement. Rao et al [18] applied GA and Taguchi methodology to optimize the drilling parameters for AlSiC MMC. Bongale et al [19] attempted to minimize wear on Al/SiCnp/E-glass fiber MMC while adopting Taguchi methodology and GA technique.…”
Section: Introductionmentioning
confidence: 99%
“…However, statistical or mathematical methods may be used to predict the Ra. Subba Rao et al applied Taguchi method for determining the appropriate parameter setting on Ra for MMC during drilling tests and they concluded that the point angle and feed have most noteworthy factors for Ra [10]. Jayaganth et al carried out the drilling experiments using various 'v', 'f' and cutting fluids as per Taguchi's orthogonal array.…”
Section: Introductionmentioning
confidence: 99%
“…Cutting force is a key part of the machining process. It can directly affect how well the material is machined and how well it is processed [ 7 ]. So, looking at the milling force of SiCp/Al composites can help us figure out how milling works and improve the accuracy of machining.…”
Section: Introductionmentioning
confidence: 99%